Relationship between platelet/lymphocyte ratio and prognosis of patients with septic acute kidney injury: A pilot study - Chen, Yu (J Chin Med Assoc, 2020)
BACKGROUND: To explore the potential role of the platelet/lymphocyte ratio (PLR) as a prognostic marker in septic patients with acute kidney injury (AKI) and to provide theoretical evidence for the epidemiological study of the prognosis of patients with septic AKI in its early stage. METHODS: A pilot study was conducted. A logistic regression analysis was conducted to screen the risk factors, and the selected factors were performed using multiple logistic regression analysis; a Receiver Operating Characteristic curve was used to determine the optimal cutoff value of the PLR and then to calculate the sensitivity and specificity of the PLR ratio. RESULTS: Mechanical ventilation, platelet count, PLR, and arterial blood lactate concentration have a correlation with sepsis (p < 0.05). An elevated PLR is significantly associated with a worse prognosis of sepsis-induced AKI (higher mortality). CONCLUSION: The PLR might be an effective factor in predicting a worse prognosis of septic AKI patients.